Kinerja Keuangan Terhadap Return Saham - Prastiani, Siti Chaerunisa; Azzahra, Khoirunnisa (Politeknik Raflesia Press, 2024)
This research aims to see the effect of financial performance on stock returns. Stock returns in this study are the dependent variable while financial performance is represented by liquidity and leverage proxies.This type of research is quantitative. The research sample is companies that issue sukuk listed on the Indonesia Stock Exchange in 2017-2021, consisting of 7 companies with five years of observation and the sample determination method used is purposive sampling. The analytical method in this research uses panel data regression analysis with a fixed effects model using Eviews version 10.0. The research results show that the variables liquidity and leverage simultaneously influence stock returns. Meanwhile, partially the Liquidity variable has an effect on Stock Returns. The leverage variable influences stock returns.